EFETUE:
(-9ay) - (-3ay)
Soluções para a tarefa
Respondido por
102
(-9ay)-(-3ay)=
-9ay+3ay=
-6ay
-9ay+3ay=
-6ay
Respondido por
10
Coloque os termos semelhantes em evidência e some ou subtraia seus coeficientes.
- Obs.: - com - = +
( - 9ay) - ( - 3ay)
- 9ay + 3ay
( - 9 + 3)ay
- 6ay
❖ AnnahLaryssa ❖
Anexos:
![](https://pt-static.z-dn.net/files/dfd/f39fb6eb84b63d02798fbc75a601ae08.jpg)
Perguntas interessantes
Português,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás
Geografia,
1 ano atrás
Geografia,
1 ano atrás